Design and fabricate two shelves file cart - Muhammad Suhail, Md Ibrahim (2009)
The file cart is a major usage to store documents and file by in order. File cart is merrily use at office or library order to make people easy to take files or documents. This file cart is taken from the concept of trolley like in the supermarket then change to the concept of file storage which makes more uses in future. With this invention, people who are short do not need to climb up the shelves to pick the documents which merrily use in daily work, which are stack up on file rack. And students at library which needs to refer to the reference book could also use this file cart. This is because students would like to have more than one reference book to refer to. So the file would come in handy. File rack is typically used for academic and industrial applications where significant volumes of physical archive material, filing or books are to be stored. Medical records at hospital storage and governmental record storage applications also make heavy use of these systems. Smaller commercial applications in file or media intensive offices such as the legal profession are common.